Cesarean Sections and Family Planning Among Ultra-Orthodox Israeli Jews - Arbel, Yuval (Journal of religion and health, 2024)
The elevated frequency of Cesarean sections (C-sections) in OECD countries not only burdens health systems financially but also heightens the risks for mothers and infants. This study explores the feasibility of reducing C-section rates by examining the Israeli ultra-Orthodox population, noted for its large families and low C-section rates. We analyze birth data from an Israeli hospital, focusing on ultra-Orthodox mothers with husbands who are yeshiva students compared to other mothers. Our findings reveal that all else being equal, mothers married to yeshiva students exhibit a lower likelihood of undergoing a C-section and a higher propensity to seek private medical services to avoid this procedure. This behavior is attributed to their preference for large families and the desire to minimize C-sections, which may restrict the number of possible future pregnancies. These insights underscore the potential effectiveness of initiatives encouraging mothers to opt for vaginal deliveries, thereby reducing healthcare costs and maternal-infant risks.